Why Replication Is Overrated. Issue 4 (December 2019) - Feest, Uljana
Abstract : Current debates about the replication crisis in psychology take it for granted that direct replication is valuable, largely focusing on its role in uncovering questionable statistical practices. This article takes a broader look at the notion of replication in psychological experiments. It is argued that all experimentation/replication involves individuation judgments and that research in experimental psychology frequently turns on probing the adequacy of such judgments. In this vein, I highlight the ubiquity of conceptual and material questions in research, arguing that replication has its place but is not as central to psychological research as it is sometimes taken to be.